one angle is acute and the other angle is obtuse
B.
they are both right angles
C.
they are both acute angles
D.
they are both obtuse angles
Answer: P(t) = 600*(1.041)^t.
Step-by-step explanation:
An exponential growth can be written as:
P(t) = A*(1 + r)^t
Where:
A = initial population = 600
r = rate of growth in decimals = 4.1%/100% = 0.041.
t = number of units of time.
Now we have a problem, we know that the growth rate is 4.1 %, but we do not know in which time units are we working.
Because is not the same if the bacteria grows a 4.1% in one day, than if the bacteria grows a 4.1% in a hour.
But that does not matter for the actual equation, because we can just define "t" as the time (like the question asks) and the equation will be:
P(t) = 600*(1 + 0.041)^t
P(t) = 600*(1.041)^t.
Answer:
{-5,15}
Step-by-step explanation:
because this function is constantly decreasing, we can get our range by looking at the endpoints:
f(-5) = 15
f(5) = -5
B. 334^x=2/3
C. (3x)^2=324
D. 3x^2=324
Answer:
Option C: (3*x)^2 = 324
Step-by-step explanation:
Janene is solving the equation:
Log₃ₓ(324) = 2
First, some rules we need to remember:
Logₙ(x) = Ln(x)/Ln(n)
and:
Ln(x^b) = b*Ln(x)
So we can rewrite our expression as:
Log₃ₓ(324) = Ln(324)/Ln(3*x) = 2
Ln(324) = 2*Ln(3*x)
Now we can use the second property:
Ln(324) = 2*Ln(3*x) = Ln( (3*x)^2 )
The arguments in both sides must be the same thing, then:
324 = (3*x)^2
This is the exponential equation she needs to solve.
Then the correct option is C.
ANSWER
d.
EXPLANATION
We want to simplify
Recall that the common logarithm has a base of 10.
This implies that,
Recall again that:
Therefore,
Answer:
no simplify. answer is:
b. log(1/7)
4(2a + 3) = 2a + 12
4(2a + 3) = 6a + 7
4(2a + 3) = 8a + 12
We want to see which one of the given expressions demonstrates the distributive property.
The correct option is the last one:
4*(2a + 3) = 8a + 12
The first thing we need to do is define the distributive property. It can be written as:
A*(B + C) = A*B + A*C
Now let's apply this to the given expression:
4*(2a + 3) = 4*(2a) + 4*3 = 8a + 12
Then we have:
4*(2a + 3) = 8a + 12
This is what we can see in the fourth option, then the correct option is the fourth one (counting from the top):
4*(2a + 3) = 8a + 12
If you want to learn more, you can read: